Analysis of the Content of Gases in Oil-Filled Equipment with Electrical Defects - Shutenko O.V. (Problems of the Regional Energetics, 2018)
Operational reliability assurance of oil-filled equipment is an urgent real-world problem, which is especially essential for the facilities that have exceeded their lifetime. The objective of the research presented is improvement in the accuracy of oil-dissolved gas analysis data interpretation when distinguishing an oil-filled equipment fault. The desired result is achieved by means of both correction of criteria values used to identify the type of fault and increase in the number of faults recognized. The research technique chosen is analysis of dissolved gas percentage, their ratio values and graphic regions for facilities under various electric faults and comparison of the obtained data with the current standard requirements. Gas concentrations have been analyzed for 906 facilities with such faults as x-wax formation, partial discharge, spark discharge, creeping discharge, low- and high-energy discharge. It has been established that with the development of defects in oil-filled equipment, the content of gases for the same defect, can differ significantly 40 types of electric fault differing in gas concentration levels, gas ratios and their graphs have been identified, which allows significantly increasing the number of distinguishable faults as compared with the current standards. Ranges of gas ratios and their percentage introduced in the paper as well as plotted graphic regions with fault type indication make it possible to recognize reliably the faults that are difficult to interpret with the current standard criteria. The presented results allow significantly increase the operational reliability of oil-filled equipment, and to reduce the costs of its maintenance and repair.